Impact of Ethiopia’s 2015 drought on child undernutrition - Hirvonen, Kalle; Sohnesen, Thomas Pave; Bundervoet, Tom (Elsevier, 2020)
In 2015, Ethiopia experienced one of its worst droughts in decades. Using nationally representative data from before and after the event, we do not find evidence that this drought led to widespread increases in chronic or acute child undernutrition. However, further analysis indicates that chronic undernutrition rates did increase in drought-exposed areas that had a limited road network. This finding suggests that the recent investments in road infrastructure in Ethiopia may have contributed towards better resilience against droughts.